Self-discovery in the dark: the demand side of industrial policy in Latin America. Issue 1 (2nd January 2016) - Fuentes, Alberto; Pipkin, Seth
ABSTRACT: Under what conditions do businesses choose to reconsider their immediate, short-term competitive niches and engage in long-term, systematic thinking by searching for new business models? This crucial question is left aside by the contemporary literature on industrial policy insofar as it assumes that the primary barrier to industrial upgrading and learning is on the 'supply side' of states facilitating private firms' pursuit of their already-established drives. We inquire into the necessary conditions for businesses' engagement with long-term thinking and innovation in contexts that reinforce preferences to stay in low-innovation, high-rent niches . Drawing from five cases in 'inertial' Latin American competitive environments where industries nevertheless voluntarily broke free of inertial trajectories to seek new approaches to business, we find that conditions of 'systemic vulnerability' – a combination of shocks in demand, sectoral comp-etitiveness and civil/social conflict – force business elites to reconsider their constituents and investment timeframes. Based on these observations, we contribute to theories of industrial policy and industrial upgrading by identifying the 'demand side' factors that affect whether firms are prepared to be competent partners in today's 'assistive, ' market-reinforcing models of industrial policy.